Prvi diplomanti in začetek novogradnje Medicinske fakultete / First graduates and building the Faculty of Medicine - Krajnc, Ivan (Acta Medico-Biotechnica, 2021)
The Faculty of Medicine, which was established with the decree to reform the University of Maribor, was unanimously accepted by the National Assembly on 2 October 2002, and will soon receive its first graduates. On 3 December 2003, the Council for Higher Education confirmed the University study program in General Medicine and announced 80 enrollment posts. The first generation of medical students enrolled in the 2004/2005 academic year, and in the 2009/2010 academic year we enrolled the first generation of the modernized and adjusted program by the Bologna declaration of a uniform master’s degree study program in General Medicine confirmed by the Council of Higher Education of Slovenia on 5 May 2008.The Faculty of Medicine is a member of University of Maribor, which is situated at Slomškov trg 15 in Maribor. On the grounds of the University Clinical Centre of Maribor, the Institute for Anatomy, Histology, and Embryology and the Institute for Physiology are located, and located next to the Institutes is our modern laboratory centre. In November, a simulation centre was opened which is the most modern such facility in this part of Europe, and in which medical students will experience a simulated setting before getting in touch with a real hospital environment.The internationally comparable uniform master’s degree study program in General Medicine offers students considerable practical work with patients under the guidance and supervision of teachers, and enables international exchange for students and professors at faculties of medicine inside and outside the European Union. Students are assured adequate basic and clinical knowledge and skills, and are educated in the sense of high ethics and proper conduct for future doctors. Our primary aim is to prepare students for the independent work of a doctor.The uniform master’s degree study program in General Medicine lasts 6 years or 12 semesters, and includes 5775 hours of theoretical and practical studies and is worth 360 ECTS points. Students have 52 obligatory subjects, but can also choose from 35 selective subjects in which they can further develop their knowledge and skills. The main characteristic of the uniform master’s degree study program in General Medicine is the tight connection of subjects inside individual study years (horizontal) and between individual study years (vertical). Problem-based learning (PBL)-modules, which in Slovenia are only carried out at our faculty, have the role of connectors. On the basis of central problems in a spiral form, they cover all areas of medicine, from knowing the basic theory and practice, efficiency in a clinical environment, and gradually attaining independence that leads students into an independent career as a doctor. Five hundred fourteen students are enrolled in all 6 study years, among them foreign students from Brazil, Croatia, Macedonia and Germany. The active international work of our young faculty must be emphasized. In this study year, 20 students are taking 1 or 2 semesters at faculties around Europe, with which we have signed agreements of cooperation. Within the student and teacher Erasmus and Tempus exchange programs, we have signed contracts with faculties and universities of medicine in the following cities: Bologna and Trieste in Italy; Aachen, Gottingen, Tubingen, Leipzig, Wurzburg, Hamburg, Mainz and Greißwald in Germany; Graz, Innsbruck, and Vienna in Austria; Oulu in Finland; Debrecen and Pecs in Hungary; Prague in the Czech Republic; Pleven in Bulgaria; Cluj Napoca in Romania; Porto and Lisabon in Portugal; Barcelona and Malaga in Spain; Tel Aviv and Jerusalem in Israel; Brussels and Ghent in Belgium, Krakow in Poland; Zagreb in Croatia; Sarajevo in Bosnia and Herzegovina; and Belgrade and Nis in Serbia. Signing agreements with further distinguished faculties are planned. It has to be said that our faculty hosts more and more students from year-to-year, especially in the clinical part of the study program.From 2005, the Faculty of Medicine of the University of Maribor has also carried out a postgraduate study program in Biomedical Technology, which is the only one of its kind in Slovenia, while it offers much content from a broader interdisciplinary scientific and research area. The individuality of the study program enables postgraduate students to construct a program which will fulfil expert and research interests of an individual in the best way.In June 2010, the first generation of students of the study program in General Medicine will graduate.Together we travelled down a long and sometimes difficult path. We give our students knowledge for their careers and appeal to their hearts to build a warm relationship with their patients.We are facing many challenges which we will be able to fulfill in the new building of the Faculty of Medicine. The new Faculty of Medicine will stand close to the University Clinical Centre of Maribor, which will make a significant contribution to the quality of work of our faculty.We expect to start construction this year and we plan to occupy the new facilities in 2012.Professor Ivan Krajnc,Dean of the Faculty of Medicine University of Maribor